Application Of System Information & Android Based Smart Display In Jewelery Stores - Christianto Gunadi; Albertus Dwiyoga Widiantoro; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2022)
In general, medium-sized retail stores have started implementing information systems to optimize their business processes, even though the information system used is relatively simple. This is not the case with precious metal retail stores or often called jewelry stores. They are currently still using manual processes.